CPEB1 enhances erastin‐induced ferroptosis in gastric cancer cells by suppressing twist1 expression. Issue 9 (12th July 2021) - Wang, Jing; Wang, Tao; Zhang, Yang; Liu, Jiaqi; Song, Jie; Han, Yanlong; Wang, Lihong; Yang, Shuang; Zhu, Lili; Geng, Rui; Li, Weimin; Yu, Xiaoguang
Abstract: The induction of ferroptosis is considered a new strategy for cancer treatment. Cytoplasmic polyadenylation element binding protein 1 (CPEB1) is a post‐transcriptional regulatory factor, whose low expression has been reported to link to the enhanced metastasis and angiogenesis of gastric cancer (GC). In this study, to explore the role of CPEB1 in ferroptosis, GC cells with overexpressed or silenced CPEB1 expression were treated with erastin, a classic ferroptosis inducer. The results showed that erastin dose‐dependently decreased the viability of four GC cell lines (AGS, SNU‐1, Hs‐746 T, and HGC‐27), suggesting that ferroptosis could be triggered in these GC cells. Interestingly, HGC‐27 cells overexpressing CPEB1 were more sensitive to erastin, generated more lipid reactive oxygen species (ROS) and malondialdehyde (MDA), and their glutathione peroxidase 4 (Gpx4) expression and GSH content were reduced. Contrarily, CPEB1‐silenced AGS cells were more resistant to erastin. Mechanically, we demonstrated that CPEB1 overexpression reduced the expression of twist1, an inhibitor of activating transcription factor 4 (ATF4), thereby activating the ATF4/ChaC Glutathione Specific Gamma‐Glutamylcyclotransferase 1 (CHAC1) pathway (CHAC1, a molecule known to induce GSH degradation). Furthermore, re‐expression of twist1 in GC cells impaired the effects of CPEB1 overexpression in presence of erastin. Additionally, similar to the in vitro results, the growth‐inhibiting effects of erastin on GC xenografted tumors were also augmented by CPEB1 overexpression in vivo. Collectively, we demonstrate that CPEB1 facilitates erastin‐induced ferroptosis by inhibiting twist1. Abstract : CPEB1 facilitated erastin‐induced ferroptosis by inhibiting twist1 and then activating the ATF4/CHAC1 pathway.